Peningkatan keterampilan pemecahan masalah matematika melalui strategi pembelajaran relating, experiencing, applying, cooperating, transfering (REACT) pada peserta didik kelas V sekolah dasar - Rizkie Ika Fauziyyah; Siti Kamsiyati; Anesa Surya (Didaktika Dwija Indria, 2020)
The purpose of this research was to improve the problem solving skills of V grade students at SDN Pajang II No. 171 Surakarta in the 2019/2020 academic year through the application of REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning strategies. This type of research is Classroom Action Research (CAR) which consists of two cycles. The subjects of this research was teachers and students in V grade, which amounted to 25 students. Data collection techniques using observation, interviews, documentation and tests. Data validity uses technical triangulation and source triangulation. Data analysis uses comparative descriptive analysis techniques, critical analysis and interactive analysis of the Miles & Huberman model. The results showed classical completeness of students in pre-action reached was 4%, in the first cycle escalate to 32%, and in the second cycle escalate again to 84%. The conclusion of this research is that the application of the REACT strategy can improve problem solving skills in V grade students of SDN Pajang II No. 171 Surakarta in the 2019/2020 academic year. This research can contribute to scientific development on problem solving skills.